Niektóre sporne problemy nowej ustawy o związkach zawodowych - Kijowski, Andrzej (Wydział Prawa i Administracji UAM, 1983)
The article consists of four parts. In the first one, the author advocates that, it is an a c t u a l position of the trade unions which is decided by practice of the system, culture and political customs, virtual relations between unions' organs and organs of the party and State and economic apparatus or by an extent of its real influence on a shape of socio-economic policies and their implementation. Legal regulation of the trade unions movement is therefore necessary, but it cannot guarantee by itself the equal position of the unions vs. the party and the State in the structure. It should be the regulation limited to the basics, not introducing specific provisions. The previous Trade Unions Act of 1 July 1949 revealed such a skeleton structure; yet, the law was not implemented in a correct way. In the second part of the article the author discusses the so-called transitional provisions of the new Act of 8 October 1982, limiting temporarily unions' rights to their discretion in assuming names and forming their organizational structures, and suspending the so-called plurality of the unions until the end of 1984. The author's attention is focused on sec. 52 of the Act prescribing loss of legal validity to the previous acts registering trade unions. In the opinion of the authorit is a political decision, and as such it has been controversial. From the legal point of view the fact that it is resulted by a legal norm (act of lawmaking) and not by an administrative act (act of law implementation) what has expliciteiy been forbidden by the convention (nr 87 of the International Labour Organization) is of no crucial importance here. As it was already expressed in the legal literature individual and specific decisions are in the discretion of administrative organs, yet in case of declaring loss of legal validity, the decision was trade by the legislative. A formal substantiation of such move could not be therefore required, while it could have been troublesome for administrative organ or court. Subjective scope of the regulation, principle of branch structure of the unions and their tasks are discussed in the third part. The tasks are still understood as the protection of rights and interests of workers, but this has to be implemented in the way complying with the conditions of the Polish system. Problems of wages for periods of strike are presented in the closing part of the article. The author advocates that the remuneration ought to be decided in the agreements terminating a strike. Sec. 45 of the Act is interpreted in this way by the author i.e. strike remuneration is not guaranteed ex lege by the new regulation but it is also not forbidden for a workplace authorities to oblige themselves to pay such a remuneration in total or in part. It is emphasised by the author in the closing remarks that limitations of union freedoms introduced by the new Act should not be left unsaid, it is necessary to explain their temporary reasons to the society and immediately withdraw these limitations as the socio-political situation in the country stabilizes.
Some controversial problems of the new trade unions act